Fatores de risco para o abandono do tratamento da tuberculose em pacientes coinfectados com HIV/AIDS em Fortaleza - Becker, Samelia Lea Menezes (2014)
People living with HIV/aids are more susceptible to TB disease due to presence of cell immunodeficiency. Besides, studies show a higher dropout rate from TB in these individuals. Fortaleza, capital of Ceara, is one of the urban centers with greater bur-den of TB in Brazil. The incidence of TB in this city is high, around 70 cases/100,000 inhabitants, and about 2,000 new cases are diagnosed each year. This study charac-terized the epidemiological patterns, and clinical risk factors for treatment dropout for tuberculosis coinfected with HIV / AIDS in the city of Fortaleza in the period 2008-2010. It was a retrospective study of case-control unpaired. Data of TB cases were obtained from 175 patients records. The software SPSS was used for statistical anal-ysis. The dropout rate of tuberculosis treatment was 28,20%. The average age was 37.5 years (SD ± 9.56), predominant in males (75.43%), single (53.14%), unem-ployed (48.01%), illiterates (6.85%) or incomplete 1st grade (52.01%), showing a scenario of socioeconomic vulnerability that permeates the TB long ago. Variables such as gender, occupation, education, smoking were not significant for the treat-ment dropout. Being married or in a stable relationship (OR = 0.49; CI = 0.24 -1.02), being new cases of tuberculosis (OR = 0.48; CI = .25-.95), use other drugs (OR = 0.25; CI = 0.12 to 0.51), present adverse reactions (OR = 0.64; CI = 0.33 to 1.26) and using HAART (OR = 0.21; CI = 0.09 to 0.49) were protective factors for abandon-ment. There was a greater chance of dropping out of treatment in those patients who consumed alcohol (OR = 1.81; CI = 0.95 to 3.42), had a diagnosis of pulmonary forms (OR = 6.25; CI = 1.78 -21.94), or disseminated (OR = 4.95; CI = 1.23 to 19.78). Illicit drug use (OR adj = 2.11; CI = 1.02 to 4.36), did not use drugs to treat opportun-istic diseases or comorbidities (OR adj = 2.87; CI = 1.28 to 6.45), and not using HAART (OR adj = 2.66; CI = 1.01 to 7.02), were conditions that together generated a higher risk for noncompliance with treatment for tuberculosis coinfection